LncRNA NEAT1 promotes angiogenesis of retinoblastoma cells through regulation of the miR-106a/HIF-1α axis - Ying Liu; Zhiyuan Xin; Kun Zhang; Xin Jin; Dajiang Wang (Heliyon, 2024)
Objective: To explore the role and mechanisms of lncRNA nuclear enriched abundant transcript 1 (NEAT1) in angiogenesis of retinoblastoma (RB) cells. Methods: This study investigated the roles of NEAT1 in RB progression. The RNA expression levels of NEAT1, miR-106a, and hypoxia-inducible factor-1alpha (HIF-1α) examined by quantitative reverse transcription polymerase chain reaction (RT-qPCR) were compared between RB cells and normal retinal pigment epithelial (RPE) cells. The binding sites between NEAT1 and miR-106a, and between miR-106a and HIF-1α were predicted by the TargetScan database and verified using the dual-luciferase reporter assay. By transfection of overexpression plasmid or shRNA of NEAT1, and/or treatment of miR-106a inhibitor or mimics, proliferation, invasion, and angiogenesis of RB cells (measured by the MTT assay, the Transwell assay, and the tube formation assay, respectively) were compared between groups. Group comparisons were analyzed using one-way analysis of variance (ANOVA), and Tukey's post-hoc test was employed for further statistical assessment. P-value less than 0.05 was considered statistically significant. Results: The RNA expression levels of NEAT1 and HIF-1α were upregulated in RB cells, whereas the expression level of miR-106a was downregulated compared with RPE cells. NEAT1 overexpression or miR-106a knockdown advanced proliferation, invasion, and tube formation of RB cells. As a target of NEAT1, miR-106a could sponge HIF-1α to downregulate HIF-1α expression level. Functional analyses indicated that miR-106a knockdown reversed the inhibitory effects of NEAT1 silencing on the proliferation, invasion, and tube formation of RB cells. Furthermore, miR-106a overexpression suppressed RB cell angiogenesis by downregulating HIF-1α expression level. Conclusion: NEAT1 promoted proliferation, invasion, and angiogenesis of RB cells through upregulation of HIF-1α expression level by sponging miR-106a, demonstrating that NEAT1 may be a novel target for RB treatment.